The DESCRIPTION OF DIATOMES EXAMINATION IN HEPARIAL ORGANS IN DROWNING CASE IN THE PELUS RIVER SOKARAJA BANYUMAS USING THE WHITE RATS (Rattus novergicus) - Imaniah, Ira; Hestiyani, Rani Afifah Nur; Hidayat, Muhammad Zaenuri Syamsu; Peramiarti, IDSAP (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Diatoms can be used to identificate and diagnose drowning cases because it can enter the body during inhaling in the water. Previous studies have shown that diatoms can be found in the liver of drowning cases, but this cannot be used as evidence of drowning cases. This study aimsto determine diatoms in the liver organs of white rats that drowned in Pelus River. This studyuses an experimental method, with 15 white rats (Rattus norvegicus) which were submerged in water from the Pelus River. Identification of diatoms in the liver was carried out using the acid destruction method. The results of the research are 9 genus of diatoms that can be identified; Amphora, Eunotia, Amphorotia, Simonsenia, Epithemia, Synedra, Ulnaria, Fragilaria, Asterionella. Meanwhile, there were only 5 genus of diatoms identified in the river water samples; Amphora, Eunotia, Craticula, Diadesmis, and Fragilaria. From this research it can be concluded that there are 9 genus of diatoms that can be identified in the livers of white rats that drowned in the fresh waters of the Pelus River